Lubrication Performance Analysis of Misaligned Journal Bearing with Roughness Surface Considering Variable Density and Variable Specific Heat - Zeng Qi; Zhou Wenping; Shen Kai (Jixie chuandong)
The thermoelastrohydrodynamic lubrication performances of misaligned journal bearing considering surface morphology,thermal effect and variable density and variable specific heat are studied. The lubrication analysis of bearing is carried out by using average flow mode based generalized Reynolds equation. The temperature field is calculated by energy equation and heat conduction equation. The results show that the effects of variable density and variable specific heat on the bearing capacity and maximum film pressure of misaligned journal are obvious when eccentricity ratio is large. The maximum film temperature is increased and power loss is decreased when considering variable density. The maximum film temperature is decreased and power loss is increased when considering variable specific heat. The higher the speed is,the greater the effect of variable density and variable specific heat on the lubrication performance is. The lubrication parameters of bearing when considering variable density and variable specific heat are obviously different from those when considering variable density or variable specific heat. The smaller the clearance is,the greater the effects of variable density and variable specific heat on the lubrication performance. In order to accurately predict the lubrication performance of bearing,the influence of variable density and variable specific heat capacity need to be considered.